ANALYSIS OF THE EFFECT OF PRACTICE AND SUPPLY CHAIN INTEGRATION ON OPERATIONAL PERFORMANCE OF SMEs IN MALANG CITY - Tirta Yoga; Djoko Koestiono; Agustina Shinta Hartati Wahyuningtyas (Agricultural Socio-Economics Journal, 2022)
This study was conducted to evaluate the practice of implementing Supply Chain Management (SCM) and Supply chain Integration (SCI) on operational performance in Small and Medium Enterprises (SMEs) in Malang City. This study aims to determine the effect of SCM practices on supply chain integration, the effect of SCM on operational performance, and the effect of supply chain integration on operational performance. Data collection in this study was carried out by distributing 100 questionnaires to owners or managers of SMEs in Malang City which the criteria are food and beverage agro-industry SMEs located in Malang City and have carried out supply chain management (SCM) activities for at least 1 year. The analytical method used in testing the research hypothesis is using multiple regression. The results of the study found that 1) there is a positive influence of supply chain management practices on operational performance, 2) there is a negative influence of supply chain integration on operational performance, 3) supply chain management practices and supply chain integration simultaneously have a positive effect on operational performance in SMEs in the Malang City.